2008
DOI: 10.1016/j.molcel.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Regulation of miRNAs Harboring Conserved Terminal Loops

Abstract: SummaryWe recently found that hnRNP A1, a protein implicated in many aspects of RNA processing, acts as an auxiliary factor for the Drosha-mediated processing of a microRNA precursor, pri-miR-18a. Here, we provide the mechanism by which hnRNP A1 regulates this event. We show that hnRNP A1 binds to the loop of pri-miR-18a and induces a relaxation at the stem, creating a more favorable cleavage site for Drosha. We found that approximately 14% of all pri-miRNAs have highly conserved loops, which we predict act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
335
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(350 citation statements)
references
References 40 publications
8
335
1
6
Order By: Relevance
“…Lin28 and hnRNP A1 interact with Drosha by binding to the terminal loop region of pri-let-7 and pri-miR-18a, respectively. 30,31 The signal transducers of the transforming growth factor β/bone morphogenetic protein, the Smads, promote the expression of a subset of miRNAs, including miR-21 and miR-199a, by facilitating the cleavage reaction by Drosha. 16,32 In response to DNA damage, p53 interacts with the Drosha processing complex through its association with DEAD-box RNA helicase p68 (also known as DDX5) and facilitates the processing of primary miRNAs to precursor miRNAs, which enhances the post-transcriptional maturation of several miRNAs with growth-suppressive function, including miR-16-1, miR-143 and miR-145.…”
Section: Discussionmentioning
confidence: 99%
“…Lin28 and hnRNP A1 interact with Drosha by binding to the terminal loop region of pri-let-7 and pri-miR-18a, respectively. 30,31 The signal transducers of the transforming growth factor β/bone morphogenetic protein, the Smads, promote the expression of a subset of miRNAs, including miR-21 and miR-199a, by facilitating the cleavage reaction by Drosha. 16,32 In response to DNA damage, p53 interacts with the Drosha processing complex through its association with DEAD-box RNA helicase p68 (also known as DDX5) and facilitates the processing of primary miRNAs to precursor miRNAs, which enhances the post-transcriptional maturation of several miRNAs with growth-suppressive function, including miR-16-1, miR-143 and miR-145.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of the six miRNAs correlate relatively well except for miR-18a, whose processing has been shown to be regulated by binding of hnRNPA1 to its conserved terminal loop. 32,42 In particular, the abundance of miR-18a is strikingly low in naive B cells. A study of miR-17-92 during mouse development also showed that expression of the individual miRNAs of the cluster did not vary entirely in parallel, 34 with miR-18a showing a disproportionate decrease in several postnatal tissues compared with the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA whose level correlated least well with the others was miR-18a ( Figure 1A and inset). Processing of this miRNA is known to be regulated by an RNA-binding protein 32 ; variation in efficiency of miR-18a processing among different cell lines is likely to be responsible for the relatively low correlation between miR-18a levels and those of the other members of the cluster. Of the 11 cell lines, the greatest amounts of miR-17-92 expression were seen in JeKo-1 (a mantle cell lymphoma line) and in DHL16 (a DLBCL line of the germinal center B-cell subtype).…”
Section: Expression Of the Mir-17-92 Cluster In B Cellsmentioning
confidence: 99%
“…Some studies indicate that the hnRNP A1 binds to the loop region of miR-18, contained in the cluster mir17-92, generating a structural rearrangement in the hairpin that promotes Drosha cleavage, favoring the independent and unique processing of miR-18. 96 The loop region of miR-18a is evolutionarily conserved, suggesting that some other well-conserved loop regions can be modulated by this mechanism (Fig. 2A).…”
Section: Drosha Processing and Alterations In Cancermentioning
confidence: 99%